UPAYA PENINGKATAN PROFESIONALISME GURU MELALUI KEGIATAN KELOMPOK KERJA GURU DI MIN 9 KOTA BANDA ACEH - Irawati Irawati (Jurnal Dedikasi Pendidikan, 2020)
One of the efforts to increase the professionalism of a teacher and develop his knowledge is through participation in the learning process in teacher working group activities (KKG). Teacher working groups (KKG) are a forum for professional activities for teachers.Based on research at the KKG in MIN 9 Banda Aceh, various problems that arise related to the KKG activities on teacher professionalism at MIN 9 Banda Aceh are focused on the following matters: 1). Lack of reliable human resources from ongoing activities. 2). The low interest of teachers in work programs arranged so that the level of participation is small. 3). The contribution of active KKG members in the activity has not been able to significantly increase teacher professionalism. The formulations of this study are: 1) How to improve teacher professionalism through teacher working group activities in MIN 9 Banda Aceh, 2) How supporting factors and inhibiting factors in efforts to increase teacher professionalism through teacher work group activities at MIN 9 Banda Aceh. This research is the field research. Data collection methods needed by the writer is devided into three types: 1) Documentation Method, 2) Observation Method, 3) Interview Method. The results of the research are divided into several indicators, are: 1) Indicators of pedagogic competence, 2) Indicators of personality competence, 3) Indicators of professional competence, 4) Indicator of social competence.